2012
DOI: 10.1002/ppap.201100162
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Characterisation of Plasma Polymerised Allyl Methacrylate Based Coatings

Abstract: Allyl methacrylate (AMA) was deposited on aluminium using atmospheric dielectric barrier discharge plasma. AMA posseses two CC bonds which have very different reactivities and the efficiency of the plasma on polymerising the two different kinds of double bonds was evaluated. The Fourier transform infrared spectra and the nuclear magnetic resonance spectra of the plasma coatings were compared with those of conventionally synthesised poly(AMA). The influence of the monomer feed on the ester, the vinyl and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…However, due to the lower reactivity of the allylic C5 5C group compared to the methacrylic group, a fully cross-linked poly(AMA) benchmark system cannot be obtained. [26,42] The propyl isobutyrate precursor (see Figure 1, (PiB)) is the fully saturated analog of AMA, and therefore cannot be polymerized through conventional polymerization reactions. Methyl methacrylate (see Figure 1, (MMA)) has one C5 5C double bond and gives rise to a linear polymer, PMMA, through conventional free radical polymerization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the lower reactivity of the allylic C5 5C group compared to the methacrylic group, a fully cross-linked poly(AMA) benchmark system cannot be obtained. [26,42] The propyl isobutyrate precursor (see Figure 1, (PiB)) is the fully saturated analog of AMA, and therefore cannot be polymerized through conventional polymerization reactions. Methyl methacrylate (see Figure 1, (MMA)) has one C5 5C double bond and gives rise to a linear polymer, PMMA, through conventional free radical polymerization.…”
Section: Methodsmentioning
confidence: 99%
“…Allyl methacrylate has a methacrylic and allylic C5 5C double bond and has been used as precursor in an atmospheric DBD reactor for the production of pdAMA films. [26][27][28][29] Based on FTIR, XPS, and solid state 13 C NMR, it was concluded that highly cross-linked pdAMA films were obtained. In comparison to AMA, the plasma deposition rate of the analogous fully saturated PiB was found to be four times lower at a constant Yasuda factor (Y f , in kJ g À1 ), i.e., input plasma power (in W) per precursor mass feed rate (in mg s À1 ).…”
Section: Introductionmentioning
confidence: 98%
“…[17,142]. These vibrations even enable discrimination, for instance, between the allyl and the vinyl groups [17].…”
Section: Page 37 Of 52mentioning
confidence: 95%
“…Because of their huge utilization in industry, oxygenated hydrocarbons such as acrylates have been widely synthesized by plasma, both at low and high pressure. References [17,28,[99][100][101][102][103][104][105][106][107][108] report XPS characterizations of some acrylate coatings (from poly(acrylic acid) to poly(methyl methacrylate)) deposited by plasma. In most of these papers, no differentiation between carboxylic acid and ester groups is envisaged and second neighbors are not necessarily considered.…”
Section: C-o or C=o In The C 1s Lineshape Fittingmentioning
confidence: 99%
See 1 more Smart Citation